Environmental, Social, and Governance Disclosure’s Impact on Return on Equity in Asian Banks - Berliana Citra Hapsari; Nessa Rifdahwati Kusuma; Hersugondo Hersugondo (Arthatama: Journal of Business Management and Accounting, 2025)
Global awareness of sustainability, social responsibility and Good Corporate Governance (ESG) is increasingly driving investor attention towards sustainable business practices, including in the Asian banking sector. However, empirical findings related to the influence of ESG on financial performance still vary. This study aims to systematically analyze the effect of ESG disclosure on the financial performance of banks in the Asian region, as measured using Return on Equity (ROE). The Systematic Literature Review (SLR) method is used to synthesize relevant empirical studies on the relationship between ESG and financial performance on relevant indexed journals in the Asian banking sector. The SLR results show that most studies have found a positive and significant influence of ESG on ROE. This study contributes to strengthening the ESG literature in the Asian financial sector and provides practical implications for banks, investors, and regulators to encourage ESG integration as a strategy to improve profitability and long-term stability.